PHYTOCHEMICAL ANALYSIS OF SOME SELECTED NDIAN MEDICINAL PLANTS - TWINKLE S. BANSODE; DR. B.K. SALALKAR (International Journal of Pharma and Bio Sciences, 2015)
Phytochemicals are bioactive compounds obtained from the plants and are widely applied in the traditional herbal medicine. These herbal medicines are used by the local people to cure the various diseases which include the major diseases such as Diabetes Mellitus, Cancer, HIV etc. The objective of the present study was to screen such a phytochemicals as well as the mineral content in selected medicinal plant extracts. Four different plants were taken for analysis viz. Trigonella foenum-graecum, Syzygium cumini, Terminalia Chebula and Salvadora persica. It was found that flavonoid is present abundantly in all species. Saponins and tannins are also present in almost all species studied. Finally among the four plant species analyzed for the mineral, we found the highest mineral content i.e. 19% in Salvadora persica plant. It was concluded that the plants studied were rich in phytochemicals with significant pharmacological and medicinal applications.